2019
DOI: 10.3390/molecules25010138
|View full text |Cite
|
Sign up to set email alerts
|

Substituted N-(Pyrazin-2-yl)benzenesulfonamides; Synthesis, Anti-Infective Evaluation, Cytotoxicity, and In Silico Studies

Abstract: We prepared a series of substituted N-(pyrazin-2-yl)benzenesulfonamides as an attempt to investigate the effect of different linkers connecting pyrazine to benzene cores on antimicrobial activity when compared to our previous compounds of amide or retro-amide linker type. Only two compounds, 4-amino-N-(pyrazin-2-yl)benzenesulfonamide (MIC = 6.25 µg/mL, 25 µM) and 4-amino-N-(6-chloropyrazin-2-yl)benzenesulfonamide (MIC = 6.25 µg/mL, 22 µM) exerted good antitubercular activity against M. tuberculosis H37Rv. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…[2][3][4][5] The synthesis of heterocycles containing pyrazine ring systems is therefore of wide interest. [6][7][8][9] The traditional method for the synthesis of pyrazines involves the use of 1,2-diketones in the presence of ammonia to produce the corresponding diamines or aminoketones followed by condensation and oxidation. [10][11][12][13] They can also be produced using -haloor hydroxy-ketones, 14,15 2H-azirines, 16 and nitro epoxides.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] The synthesis of heterocycles containing pyrazine ring systems is therefore of wide interest. [6][7][8][9] The traditional method for the synthesis of pyrazines involves the use of 1,2-diketones in the presence of ammonia to produce the corresponding diamines or aminoketones followed by condensation and oxidation. [10][11][12][13] They can also be produced using -haloor hydroxy-ketones, 14,15 2H-azirines, 16 and nitro epoxides.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature survey, it was found that these type of compounds can bind to the matrix metalloproteinase-8 (MMP-8; also known as neutrophil collagenase; PDB ID: 5h8x) [ 47 , 48 ]. This endopeptidase is part of a complex proteolytic MMP enzyme family, where its over expression has been linked to several pathological processes [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, all analogues (1-5) showed inhibitory concentrations of 50% (IC 50 ) and grown inhibitory concentrations of 50% (GI 50 ) >100.0 μg/ml À1 against gram-positive bacteria, gram-negative bacteria, and all analyzed tumor (MCF-7, HCT 116, A549) cell lines (Bhat et al, 2020). Against Mtb (H 37 Rv), Bouz and co-workers (2020) synthetized and assessed the following: Mycobacterium kansasii; Mycobacterium avium; Mycobacterium smeg; and Mycobacterium aurum, a series bearing N-(pyrazin-2-yl) benzenesulfonamide-based analogues (Bouz et al, 2020). Two of these compounds (6-7) presented MIC values of 6.25 μg/ml À1 against Mtb (Figure 3); they (6-7) also showed MIC ranges of 1.56 μg/ml À1 (6) and 12.5 μg/ml À1 (7) against Mycobacterium kansasii, 100.0 μg/ml À1 (6) and 25.0 μg/ml À1 (7) against F I G U R E 3 Novel N-(Pyrazin-2-yl)benzene-based sulfonamide analogues (6-7) (Bouz et al, 2020) (Brown et al, 2019) F I G U R E 5 New Ntrifluoromethylthiolated-based sulfonimidamides/sulfoximines analogues (28-43) (Thota et al, 2019) F I G U R E 6 Novel indazolebased sulfonamide analogues (44-50) (Park et al, 2017) Mycobacterium avium, ≥500.0 μg/ml À1 (6) and ≥ 500.0 μg/ml À1 (7) against Mycobacterium smeg, and 250.0 μg/ml À1 (6) and 250.0 μg/ml À1 (7) against Mycobacterium arum (Bouz et al, 2020).…”
Section: Sulfonamide-based Conjugatesmentioning
confidence: 99%
“…Against Mtb (H 37 Rv), Bouz and co-workers (2020) synthetized and assessed the following: Mycobacterium kansasii; Mycobacterium avium; Mycobacterium smeg; and Mycobacterium aurum, a series bearing N-(pyrazin-2-yl) benzenesulfonamide-based analogues (Bouz et al, 2020). Two of these compounds (6-7) presented MIC values of 6.25 μg/ml À1 against Mtb (Figure 3); they (6-7) also showed MIC ranges of 1.56 μg/ml À1 (6) and 12.5 μg/ml À1 (7) against Mycobacterium kansasii, 100.0 μg/ml À1 (6) and 25.0 μg/ml À1 (7) against F I G U R E 3 Novel N-(Pyrazin-2-yl)benzene-based sulfonamide analogues (6-7) (Bouz et al, 2020) (Brown et al, 2019) F I G U R E 5 New Ntrifluoromethylthiolated-based sulfonimidamides/sulfoximines analogues (28-43) (Thota et al, 2019) F I G U R E 6 Novel indazolebased sulfonamide analogues (44-50) (Park et al, 2017) Mycobacterium avium, ≥500.0 μg/ml À1 (6) and ≥ 500.0 μg/ml À1 (7) against Mycobacterium smeg, and 250.0 μg/ml À1 (6) and 250.0 μg/ml À1 (7) against Mycobacterium arum (Bouz et al, 2020). For these compounds, cytotoxicity analysis was performed against hepatocellular carcinoma (HepG2) lines, demonstrating IC 50 values of 775.6 μg/ml À1 (6) and > 500.0 μg/ml À1 (7) (Bouz et al, 2020).…”
Section: Sulfonamide-based Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation